Polar engineering regulates photoluminescence-tunable carbon dots for microalgal lipid imaging. Issue 21 (22nd August 2022) - Fu, Fangmei; Huang, Sirui; Pan, Xiaoqin; Lin, Junjie; Huang, Xiaoman; Liang, Zishan; Zeng, Guiling; Li, Wei; Zhang, Haoran; Zhang, Xuejie; Zheng, Mingtao; Zheng, Yinjian; et al.
Abstract : Synthesis and purification of three carbon dots and the application of R-CDs in microalgae lipid imaging. Abstract : At present, research on the regulation strategy and mechanism of carbon dots (CDs) fluorescence emission from short wavelength to long wavelength is a hot topic. Herein, o -phenylenediamine (O-PDA) was used as the sole precursor and the polarity of the reaction solvent was adjusted by changing the volume ratio of N, N -dimethylformamide (DMF) to H2 O to synthesize green (G-CDs), orange (O-CDs), and red CDs (R-CDs). All three types of CDs exhibited uniform particle sizes and excitation-independent photoluminescence (PL) emissions. The fluorescence lifetime decay curves revealed that the emission centers of G-CDs to O-CDs or R-CDs changed from double-emission centers to pure surface emission, which led to their different solvatochromic effects. X-Ray photoelectron spectroscopy (XPS), nuclear magnetic resonance spectroscopy (NMR), and mass spectroscopy (MS) techniques proved that the appropriate polarity of the reaction solvent could extend the π-conjugation of the fluorescent molecular structure on the surface of the CDs and induce a red-shift of the CDs emission. In addition, R-CDs had a relatively large nonpolar aromatic structure that showed low polarity and lipophilicity. The R-CDs dispersed in glycerol trioleate showed bright yellow fluorescence with a quantum yield (QY) of 43.52% but almost no fluorescence in water. At the same time, R-CDs had the advantages of good biocompatibility, a large Stokes shift (113 nm), and excellent photostability. Finally, as a targeted probe of microalgae lipids, R-CDs could screen the microalgae lipid-rich varieties and monitor changes in microalgae lipid content under N-free culture conditions.